Reviewing the constitution? - Khanna, D.D. (ed.); Kueck, Gert W. (ed.) (New Delhi, 2000)
The book contains contributions from some of the most outstanding Indian, German, French, British and Japanese constitutional experts. It should serve as a prologue or background document of immense value to any honest examination or review of the working of the Constitution. All those interested in the theme should find it an indispensable reading.
Keywords: Constitutions-India